Relational theory for computer professionals a technical tutorial - Date, C. J. (O'Reilly Media, 2013)
"All of today's mainstream database products support the SQL language, and relational theory is what SQL is supposed to be based on. But are those products truly relational? Sadly, the answer is no. In this video, Chris Date shows you what a real relational product would be like, and how and why it would be so much better than what's currently available."--Resource description page.